Epidemiological Observations on Cryptosporidiosis in Diarrheic Goat Kids in Greece - Nektarios D. Giadinis (Veterinary Medicine International, 2015)
This study aimed at investigating the occurrence of Cryptosporidium spp. in diarrheic goat kids in Greece and the risk factors associated with cryptosporidiosis. Altogether, 292 diarrheic 4–15-day-old goat kids from 54 dairy goat herds of Northern Greece were examined. Oocysts of Cryptosporidium spp. were detected in 223 of 292 (76.4%) goat kids and the intensity of infection was scored as “high” in 142 samples, “moderate” in 45 samples, and “low” in 36 samples. Larger herds (>200 animals) had higher infection rates than smaller ones, although this difference was not statistically significant. Significantly higher infection rates were observed in herds during late kidding season (1 January to 30 April) compared to the early one (1 September to 31 December). These results suggest that cryptosporidiosis is very common in diarrheic goat kids in Greece, especially in large herds during the late parturition season.